2019
DOI: 10.1121/1.5139640
|View full text |Cite
|
Sign up to set email alerts
|

Observation of selective optical manipulation of particles in acoustic levitation

Abstract: Acoustic Radiation Force is commonly used to create stable large-scale aggregates of particles in levitation (so-called “acoustic levitation”) in a micro-cavity. The authors show in the following work that this well-known and well-controlled aggregation process can be reversed without contact or external flow if the aggregated particles are enlightened with the proper optical wavelength. This coupled optics and acoustics effect has been observed with various kinds of particles and different optic wavelengths, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Indeed the acoustic trap breakup by light has been experimentally observed. [ 30 ] We found that the particle‐ejection effect by light is more likely on 10 μm beads with laser intensities greater than 5 mW.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed the acoustic trap breakup by light has been experimentally observed. [ 30 ] We found that the particle‐ejection effect by light is more likely on 10 μm beads with laser intensities greater than 5 mW.…”
Section: Resultsmentioning
confidence: 99%
“…[ 29 ] A confocal microscope takes the Raman spectrum of single polystyrene particles with virtually no interference of the device parts. We also observed the ejection of 10 μm particles from the aggregate's periphery [ 30 ] as a result of the laser interaction.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, when the spherical symmetry assumption of the manipulated objects is no longer satisfied, such as with disks 15 or metallic micro-cylinders [16][17][18][19][20] , particles are actively propelled by the acoustic forces instead of quietly aggregating into stable positions. Unexpected effects can also arise when using particles with specific properties, such as hollow core particles 21,22 or specific optical properties 1 , which is the present study object.…”
Section: Introductionmentioning
confidence: 99%
“…Influence of the temperature on the opto-acoustophoretic effect Gabriel Dumy, 1, a) Mauricio Hoyos, 1 and Jean-Luc Aider 1 Laboratory PMMH, ESPCI Paris PSL, Sorbonne Université Opto-acoustophoretic mobility has been demonstrated recently for fluorescent and colored particles acoustically levitated in a stationary ultrasonic field, when illuminated with the appropriate optical wavelength 1,2 . It is a repeatable phenomenon, needing both acoustic trapping and specific optic excitation to occur.…”
mentioning
confidence: 99%
“…on the application, the acoustic forces can be combined with other forces like flow viscous drag (Petersson et al, 2007), optical (Dumy et al, 2019), or gravity ones (Wiklund et al, 2004). Acoustophoresis is used as a robust method for concentrating (Carugo et al, 2014;Dron et al, 2009;Nordin and Laurell, 2012), washing (Augustsson and Laurell, 2012), separating (Ding et al, 2014;Petersson et al, 2007), or trapping (Evander and Nilsson, 2012;Jeger-Madiot et al, 2021) cells.…”
mentioning
confidence: 99%